COPD in never smokers - Salvi, Sundeep (Henry Stewart Talks, 2012)
Non-smoking risk factors, Indoor air pollution, especially biomass fuel, burning of mosquito coil, Outdoor air pollution, Occupational causes, Poorly treated asthma, Post pulmonary tuberculosis, Early life environmental factors, especially nutrition and socio-economic factors, Need for more research and better understanding in this field